Kualitas Pelayanan Pembuatan Paspor di Kantor Imigrasi Kelas I Tempat Pemeriksaan Imigrasi (TPI) Samarinda - Meyke Iim Wulandari; Iman Surya; Muhammad Hairul Saleh (Jurnal Ilmu Pemerintahan, 2023)
This study aims to determine the quality of passport making services at the Samarinda Class I TPI Immigration Office, and to find out the obstacles faced by the Samarinda Class I TPI Immigration Office in providing services to passport applicants. This research was conducted at the Immigration Office Class I Immigration Checkpoint (TPI) Samarinda. This type of research is descriptive qualitative. Data collection is done by means of library research and field research with qualitative descriptive analysis. By basing on existing data, the author describes systematically, factually and accurately about the facts, characteristics and relationships between existing phenomena. The results showed that the quality of passport-making services carried out by the Samarinda Class I TPI Immigration Office was already going well, starting from the beginning of the process of implementing passport-making services, the officers worked quite well and were able to direct passport applicants. However, in terms of online registration there are still obstacles such as difficulty entering or difficulty downloading proof of payment to centralized network disruptions that sometimes hinder the passport making process at the Samarinda Class I TPI Immigration Office, then the facilities and infrastructure are quite good as seen from the availability of waiting rooms such as chairs, tvs, children's playgrounds, toilets that are quite clean, then prayer rooms but there are still shortcomings, especially in the parking area which is inadequate as evidenced by the fact that there is still a lot of parking space.